Tuning azoheteroarene photoswitch performance through heteroaryl design - Calbo,J; Weston,CE; White,A; Rzepa,H; Contreras-García,J; Fuchter,MJ (Journal of the American Chemical Society, 2016)
Photoswitchable compounds, which can be reversibly switched between two isomers by light, continue to attract significant attention for a wide array of applications. Azoheteroarenes represent a relatively new but understudied type of photoswitch, where one of the aryl rings from the conventional azobenzene class has been replaced with a five-membered heteroaromatic ring. Initial studies have suggested the azoheteroarenes - the arylazopyrazoles in particular - to have excellent photoswitching properties (quantitative switching and long Z isomer half-life). Here we present a systematic computational and experimental study to elucidate the origin of the long thermal half-lives and excellent addressability of the arylazopyrazoles, and apply this understanding to determine important structure-property relationships for a wide array of comparable azoheteroaryl photoswitches. We identify compounds with Z isomer half-lives ranging from seconds to hours, to days and to years, and variable absorption characteristics; all through tuning of the heteraromatic ring. Conformation perhaps plays the largest role in determining such properties; where the compounds with the longest isomerization half-lives adopt a T-shaped ground state Z isomer conformation and proceed through a T-shaped isomerization pathway, whereas the most complete photoswitching is achieved for compounds that have a twisted (rather than T-shaped) Z-isomer conformation. By balancing these factors, we report a new azopyrazole 3pzH, which can be quantitatively switched to its Z-isomer (>98%) with 355 nm irradiation, near-quantitatively (97%) switched back to the E isomer with 532 nm irradiation, and has a very long half-life for thermal isomerisation (t1/2 = 74 d at 25 °C). Given the large tunability of their properties, the predictive nature of their performance, and the other functional opportunities afforded by usage of a heteroaromatic system, we believe the azoheteroaryl photoswitches to have huge potent